Perceived Usefulness of Google Scholar for Literature Review and Intention to Use: Evidence From Rizal Technological Office Administration Students - Cheska Nadine Rodriguez; Dianna Mae N. Tagapia; Rachell Mae R. Ureña; Jayvie O. Guballo (The Indonesian Institute of Science and Technology Research, 2026)
This study aims to examine the perceived usefulness of Google Scholar among Office Administration students in state universities, focusing on its role in conducting literature reviews. The research seeks to measure factors that drive students to use Google Scholar, associated with students' intentions to continue using the platform in their academic work. The study specifically gathered data from Office Administration students enrolled in state universities during the academic year 2024-2025. Findings from this research will contribute to improving digital literacy programs and enhancing students’ academic experience. The study revealed a significant correlation between the perceived usefulness of Google Scholar and students’ intention to use it. It shows that the multiple factors, such as efficiency in finding relevant sources, quick access to information, availability of up-to-date research, user-friendliness, and cost-free access, are associated with students' intention to use Google Scholar for their academic research, especially in finding literature reviews. The strong positive correlations across various aspects indicate that students who perceive Google Scholar as a useful tool are more inclined to integrate it into their research activities, prefer it over other academic databases, explore its advanced features, and recommend it to others. The findings show that while students find Google Scholar convenient and accessible, some struggle with navigation and accessing full-text articles. The study recommends further research on the platform’s long-term impact and how digital literacy affects its use. Future studies may explore whether targeted training improves students' research skills, offering insights for universities to better support academic success.